The interactive of Pendidikan Islam courseware using ADDIE method / Mohammad Faris Che Ya - Che Ya, Mohammad Faris (2015)
Pendidikan Islam is one of the subjects taught at pre-school and it becomes one of the important subjects in order to introduce about Islam to the pre-school children. Realize of great influence to the pre-school children to learn Pendidikan Islam at their early age, developing a courseware as a complementary subject is a reason why the prototype is developed. The study is to develop a prototype of Pendidikan Islam courseware based on the syllabus of the subject itself The ADDIE model is used as a guideline in order to develop the prototype. The method used in this study is by distributing a questionnaire to the pre-school teachers to get a feedback and information related to the study. Through the data gathered, researcher indicates that there are many pre-school teachers agreed using the courseware as a complementary subject can influence children to learn more effectively.